Does Foreign Ownership Increase Financial Reporting Quality? - Yohan An, Yohan An (Asian Academy of Management (AAM), 2015)
Using panel data, this paper investigates how foreign ownership affects the financial reporting quality of firms listed on the Korean Stock Exchange (KSE), one of the highest foreign-investor capital markets in the world during the period from 2000 to 2005. Existing studies suggest that foreign ownership may either increase or decrease the quality of financial reporting, suggesting that foreign ownership is explained using two conflicting hypotheses: The active-monitoring hypothesis and the transient hypothesis. In emerging markets, where family ownership is predominant, conservatism is an important measure of financial reporting quality because conservatism decreases opportunistic management behaviours and mitigates information asymmetries. This paper tests conservatism as a proxy for financial reporting quality using three piecewise accrual models, proposed by Ball and Shivakumar (Journal of Accounting Research, 44, 207–256 (2006)); the cash flow model, the Dechow and Dichev model, and the Jones model. This research finds that foreign ownership is positively associated with conservatism in all three models. This result supports the active-monitoring hypothesis of foreign ownership, indicating that foreign ownership mitigates managerial opportunism, thereby increasing the quality of financial reporting